Dynamics of cellular states of fibro-adipogenic progenitors during myogenesis and muscular dystrophy - Barbora Malecova (Nature Portfolio, 2018)
Fibro-adipogenic progenitors (FAPs) resident in skeletal muscle are involved in both regeneration and maladaptive processes. Here, the authors identify subpopulations of FAPs with biological activities implicated in physiological muscle repair that are altered in pathological conditions such as muscular dystrophies.